2004
DOI: 10.1210/en.2003-1166
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response to Exogenous and Endogenous Myostatin in Myoblasts Suggests that Myostatin Acts as an Autocrine Factorin Vivo

Abstract: Myostatin is a member of the TGF-beta superfamily that is essential for proper regulation of skeletal muscle growth. As do other TGF-beta superfamily members, myostatin signals into the cell via a receptor complex that consists of two distinct transmembrane proteins, known as the type I and type II receptors. Vertebrates have seven distinct type I receptors, each of which can mix and match with one of five type I receptors to mediate signals for all the TGF-beta family ligands. Accumulating evidence indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 39 publications
3
49
0
2
Order By: Relevance
“…For instance, under starvation conditions, TORC1 is responsible for up-regulating autophagy, a process that generates energy by degrading portions of the cytoplasm (Neufeld 2010;Ravikumar et al 2010). A number of studies have demonstrated that myostatin acts as a negative regulator of mTOR-directed signalling, which is consistent with its inhibitory effect on protein synthesis (Amirouche et al 2009;Langley et al 2002;Lipina et al 2010;McFarlane et al 2006;Rios et al 2004;Sartori et al 2009;Trendelenburg et al 2009) and more specifically on protein translation in skeletal muscle (Trendelenburg et al 2009). On the other hand, myostatin deletion is beneficial for bone density, insulin sensitivity and heart function in senescent mice (Morissette et al 2009), and inhibition of ActRIIB, the cell membrane receptor for which myostatin has the highest affinity (Sakuma and Yamaguchi 2012), increases survival (by 17 %) in myotubularin-deficient mice, due to a delay in the point at which animals experience weight loss or complete hind limb paralysis (Lawlor et al 2011) (X-linked myotubular myopathy is a severe form of congenital myopathy which most often manifests with severe perinatal weakness and respiratory failure).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For instance, under starvation conditions, TORC1 is responsible for up-regulating autophagy, a process that generates energy by degrading portions of the cytoplasm (Neufeld 2010;Ravikumar et al 2010). A number of studies have demonstrated that myostatin acts as a negative regulator of mTOR-directed signalling, which is consistent with its inhibitory effect on protein synthesis (Amirouche et al 2009;Langley et al 2002;Lipina et al 2010;McFarlane et al 2006;Rios et al 2004;Sartori et al 2009;Trendelenburg et al 2009) and more specifically on protein translation in skeletal muscle (Trendelenburg et al 2009). On the other hand, myostatin deletion is beneficial for bone density, insulin sensitivity and heart function in senescent mice (Morissette et al 2009), and inhibition of ActRIIB, the cell membrane receptor for which myostatin has the highest affinity (Sakuma and Yamaguchi 2012), increases survival (by 17 %) in myotubularin-deficient mice, due to a delay in the point at which animals experience weight loss or complete hind limb paralysis (Lawlor et al 2011) (X-linked myotubular myopathy is a severe form of congenital myopathy which most often manifests with severe perinatal weakness and respiratory failure).…”
Section: Discussionmentioning
confidence: 82%
“…The mTOR pathway is an evolutionarily conserved nutrient-sensing pathway that adjusts metabolism and growth to amino acid availability, growth factors, energy status and stress (Fenton and Gout 2011;Sengupta et al 2010). A number of studies have demonstrated that myostatin acts as a negative regulator of mTOR-directed signalling (Amirouche et al 2009;Langley et al 2002;Lipina et al 2010;McFarlane et al 2006;Rios et al 2004;Sartori et al 2009;Trendelenburg et al 2009), which provides support for a potential role of myostatin inhibition in longevity. Myostatin deletion is in fact beneficial for bone density, insulin sensitivity and heart function in senescent mice (Morissette et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Because the activation of type I receptor induces phosphorylation of an intracellular effector, Smad2 (20,21), we investigated whether the level of Smad2 phosphorylation is affected by caveolin-3. COS-7 cells transfected with either the wild-type or the P104L mutant caveolin-3 were stimulated with recombinant myostatin.…”
Section: Caveolin-3 Negatively Regulates Activation Of the Type I Myomentioning
confidence: 99%
“…The circulating active form of myostatin directly binds to and activates activin receptor IIB (ActRIIB), a type II serine/threonine kinase receptor (19). This, in turn, activates the type I serine/threonine kinase receptor activin receptor-like kinase 4 (ALK4) or ALK5 at the plasma membrane (20,21). The activation of a heteromeric receptor complex consisting of type II and type I serine/threonine kinase receptors induces the phosphorylation of intracellular effectors Mad homolog 2 (Smad2) and Smad3 (20,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation